1999
DOI: 10.1016/s0042-6989(98)00165-5
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral and central delay in processing high spatial frequencies: reaction time and VEP latency studies

Abstract: Visually evoked potentials (VEP) and reaction time (RT) were recorded under stimulation with sinusoidal gratings. Grating spatial frequency (SF) was 0.5, 5 or 12 cd and grating contrast was varied. Consistent with previous findings, both VEP latency and RT increased with the increase of grating SF and with the decrease of grating contrast. It was found, in addition, that RT and VEP latency increased by approximately the same amount when SF increased from 0.5 to 5 cd, thus suggesting that the main source of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
30
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(40 citation statements)
references
References 28 publications
10
30
0
Order By: Relevance
“…The delay value was estimated as the difference between the actual RT and the detection latency estimated by each model, averaged over all thee coherence levels. For the peak detector model, the slopes were much smaller than 1 (0.190 Ϯ 0.092), which is in agreement with previous reports (Osaka and Yamamoto, 1978;Musselwhite and Jeffreys, 1985;Mihaylova et al, 1999;Patzwahl and Zanker, 2000;Kawakami et al, 2002;Vassilev et al, 2002). For the level detector model, the slopes were increased but were not sufficiently close to 1 (0.810 Ϯ 0.122).…”
Section: Resultssupporting
confidence: 90%
See 2 more Smart Citations
“…The delay value was estimated as the difference between the actual RT and the detection latency estimated by each model, averaged over all thee coherence levels. For the peak detector model, the slopes were much smaller than 1 (0.190 Ϯ 0.092), which is in agreement with previous reports (Osaka and Yamamoto, 1978;Musselwhite and Jeffreys, 1985;Mihaylova et al, 1999;Patzwahl and Zanker, 2000;Kawakami et al, 2002;Vassilev et al, 2002). For the level detector model, the slopes were increased but were not sufficiently close to 1 (0.810 Ϯ 0.122).…”
Section: Resultssupporting
confidence: 90%
“…Although some EEG studies have suggested that the latency of the peak response changes in parallel with the manual RT (Vaughan et al, 1966;Jaskowski et al, 1990), most EEG/MEG studies (Osaka and Yamamoto, 1978;Musselwhite and Jeffreys, 1985;Mihaylova et al, 1999;Patzwahl and Zanker, 2000;Kawakami et al, 2002;Vassilev et al, 2002), including the present one (Figs. 2 and 6), indicate that the change in the peak latency is too small to account for the change in RT (peak detector model).…”
Section: Model Comparisonmentioning
confidence: 67%
See 1 more Smart Citation
“…The observation of typical VEP latencies for pattern reversal at high and low luminance contrast documents consistency of the visual presentation via LCD goggles during simultaneous BOLD MRI and efficacy of the postprocessing software for gradient and cardioballistic artifact reduction (33,34). Additionally, visual stimulation by motion onset led to a prominent N2 component over left temporal derivations at a latency of 180 ms. Again, this finding is in line with previous observations of N2 as a highly sensitive correlate to contrast and motion (16,18,35).…”
Section: Discussionsupporting
confidence: 54%
“…Similarly, previous studies have reported that contrast affects reaction times for detecting both stimulus and motion onset for sinusoidal gratings (Burr et al 1998;Harwerth and Levi 1978;Lupp et al 1976;Mihaylova et al 1999;Tartaglione et al 1975). The contrast effect on simple reaction times for detecting stationary sinusoidal gratings has a mean slope increase of about 8 ms per log 2 contrast decrease at 0.5 cpd (Fig.…”
Section: Time Delaysupporting
confidence: 53%